Increased average longevity among the "Tour de France" cyclists - Sanchis-Gomar, F.; Olaso-Gonzalez, G.; Corella, D.; Gomez-Cabrera, M. C.; Vina, J. (International Journal of Sports Medicine, 2011)
It is widely held among the general population and even among health professionals that moderate exercise is a healthy practice but long term high intensity exercise is not. The specific amount of physical activity necessary for good health remains unclear. To date, longevity studies of elite athletes have been relatively sparse and the results are somewhat conflicting. The Tour de France is among the most gruelling sport events in the world, during which highly trained professional cyclists undertake high intensity exercise for a full 3 weeks. Consequently we set out to determine the longevity of the participants in the Tour de France, compared with that of the general population. We studied the longevity of 834 cyclists from France (n=465), Italy (n=196) and Belgium (n=173) who rode the Tour de France between the years 1930 and 1964. Dates of birth and death of the cyclists were obtained on December 31st 2007. We calculated the percentage of survivors for each age and compared them with the values for the pooled general population of France, Italy and Belgium for the appropriate age cohorts. We found a very significant increase in average longevity (17%) of the cyclists when compared with the general population. The age at which 50% of the general population died was 73.5 vs. 81.5 years in Tour de France participants. Our major finding is that repeated very intense exercise prolongs life span in well trained practitioners. Our findings underpin the importance of exercising without the fear that becoming exhausted might be bad for one's health.